Characterisation and potential applications of Serratia odorifera INTA L401-1 in nematode biocontrol - Salas, Augusto; Ortiz, Leila Melina; Niz, José María; Magariños, Francisco; Del Valle, Eleodoro Eduardo; Achinelly, María Fernanda; Sauka, Diego Hernan (Taylor & Francis, 2025)
The increasing demand for sustainable agriculture has driven the search for biological control agents targeting plant-parasitic nematodes. This study characterised Serratia odorifera strain INTA L401-1, isolated for the first time from the hemolymph of Tenebrio molitor larvae infected with Heterorhabditis bacteriophora, and evaluated its nematicidal activity. Phylogenetic analysis using 16S rRNA sequencing, along with phenotypic profiling, identified the strain as S. odorifera with 99% confidence. In vitro bioassays demonstrated significant activity against Panagrellus redivivus, with 24-hour-old cultures achieving 89.1% mortality on nutrient agar, attributed to peak secondary metabolite production. Mortality declined in 48–72-hour-old cultures but increased after seven days, likely due to metabolite accumulation. Filtered supernatants of nutrient broth cultures retained nematicidal activity (>40%), implicating secreted metabolites as the primary factors, while volatile organic compounds showed no activity. Greenhouse experiments with Meloidogyne incognita in tomato plants showed improved growth parameters (fresh root and shoot weight) with supernatant treatment, though nematode reduction was not statistically significant. Whole-genome sequencing of INTA L401-1 produced a 4.96 Mb draft genome, confirming its identity and revealing genes encoding nematicidal proteins (e.g. serralysin, chitinases) and bioactive compounds (e.g. serrawettins, siderophores). These findings highlight its dual roles in nematode control and plant growth promotion. The isolation of INTA L401-1 from an unusual niche raises questions about its ecological role, whether as an endosymbiont or an environmental acquisition. Field trials are needed to validate its potential as a biocontrol agent and plant growth-promoting bacterium for sustainable agriculture.